Inovasi dalam Pelatihan dan Pengembangan Karyawan Serta Memperkuat Fondasi Manajemen SDM Unggul di Era Globalisasi - Zhafira Aini; Sanisah Sanisah; Marlina Marlina (Lembaga Pengembangan Kinerja Dosen, 2024)
When globalization brings significant changes to the business world, companies must strengthen their advanced human resource management foundations through innovation in employee training and development. Given the dynamics of change and intense competition, human resource training and development are becoming increasingly crucial. Effective training enhances individuals' skills while fostering an organizational culture that supports innovation and learning. Companies can gain a competitive advantage by enhancing their employees' ability to adapt to change through the implementation of inventive HR training approaches.